A Study of the Validity of Mujahid Ibn Jabr's Interpretation in the Interpretation of the Qur'an - ‘Ulya, Nurul Shifatul (Journal of Ulumul Qur'an and Tafsir Studies, 2025)
Mujahid ibn Jabr (d. 102 AH) is one of the most prominent tabiʿīn scholars whose tafsir has had a lasting influence on the development of Qur’anic exegesis. As a close student of Ibn ʿAbbās, Mujahid became a key transmitter of tafsīr bi al-maʾthūr, emphasizing narrations from the Prophet, his Companions, and early generations. His work, although not systematically codified in his lifetime, was later compiled and became one of the earliest references in Qur’anic interpretation. This study examines the methodology and validity of Mujahid’s exegesis through textual analysis and critical evaluation of sanad and matn. The findings indicate that while his interpretations include strong, weak, and even very weak chains of transmission, they remain widely accepted among classical and modern scholars, particularly when consensus exists among the tabiʿīn. Mujahid’s ijmālī style, combining concise explanation with occasional ijtihād, demonstrates both his fidelity to transmitted knowledge and his openness to reasoned interpretation. This underscores the enduring importance of his tafsir in the historiography of Qur’anic studies and highlights its relevance for contemporary scholarship.